"We the People": Epistemological Moves Through Cultural Praxis. (June 2019) - Quijada Cerecer, David Alberto; Cahill, Caitlin; González Coronado, Yvette Sonia; Martinez, Jarred
How do young people embody activism and artistic praxis as they commit to community-based participatory action research for social change? We consider how the arts might provide a social and shared context for challenging racialized characterizations. Our analysis draws upon arts-based participatory action research projects conducted by the Mestizo Arts & Activism Collective (https://maacollective.org ), a social justice think tank led by the urgent concerns of young people of color. Specifically, we engage the arts as integral to the research process—an epistemological move that opens up new ways of understanding and knowing our world and representing ourselves.